1987
DOI: 10.1113/jphysiol.1987.sp016724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of central or peripheral axotomy on membrane properties of sensory neurones in the petrosal ganglion of the cat.

Abstract: SUMMARY1. The properties of sensory neurones in the petrosal ganglion of the cat were examined in vitro with intracellular electrodes 8 days after section of the central (bulbar roots) or peripheral process. Two types of cells, both with conduction velocities faster than 2 m/s and with humps on the falling phases of their action potentials (H-neurones), were studied: glossopharyngeal neurones arising from the tongue and pharynx, and carotid neurones originating in the carotid body and carotid sinus.2. Peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…These changes include altered excitability of the somadendritic compartment and axon initial segment (17,19), which involves Na-dependent electrogenesis (22,23). While these early experiments were interpreted as suggesting a shift in vectorial transport of channels in axotomized neurons (21,24), our results indicate that an altered pattern of gene expression contributes to the electrophysiological changes.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These changes include altered excitability of the somadendritic compartment and axon initial segment (17,19), which involves Na-dependent electrogenesis (22,23). While these early experiments were interpreted as suggesting a shift in vectorial transport of channels in axotomized neurons (21,24), our results indicate that an altered pattern of gene expression contributes to the electrophysiological changes.…”
Section: Discussionmentioning
confidence: 60%
“…Altered neuronal excitability has been demonstrated following axonal transection (17)(18)(19) and may underlie abnormal DRG bursting associated with pain syndromes (9,20). Abnormal somatodendritic excitability following axotomy is Na dependent (21,22), and it has been suggested that this is due to a shift, following axotomy, in vectorial transport of Na channels (23,24).…”
mentioning
confidence: 99%
“…However, the changes in electrophysiological properties after axotomy are variable and depend on the type of neuron as well as the organism. For example, in cat and rat, injured dorsal root ganglia (DRG) neurons display a decrease in the amplitude and duration of the afterhyperpolarization (AHP) (Gallego et al, 1987;Sapunar et al, 2005), whereas the duration of AHPs in injured DRG neurons in hamster (Gurtu and Smith, 1988) or mouse (Liu et al, 2002) does not change.…”
Section: Introductionmentioning
confidence: 99%
“…Excitability and Na current density are altered in neurons after axonal injury (22)(23)(24)(25). After axotomy, rat DRG neurons display dramatic changes in their TTX-R and TTX-S Na currents and in their Na channel mRNA profile; these changes include an attenuation of TTX-R and enhancement of TTX-S Na currents (21, 26), down-regulation of SNS͞PN3 transcripts and up-regulation of ␣III transcripts (20), and moderate elevation in the levels of ␣I and ␣II mRNAs (27).…”
Section: Introductionmentioning
confidence: 99%